Back pain and body posture of non-professional Brazilian Jiu-Jitsu practitioners - Sędek, Katarzyna; Truszczyńska-Baszak, Aleksandra; Cygańska, Anna Katarzyna; Drzał-Grabiec, Justyna (PeerJ, 2022)
Background The aim of the study was to assess the prevalence of back pain in non-professional Brazilian Jiu-Jitsu practitioners (NP-BJJ practitioners), and to assess the relationship between their back pain and postural disorders. Methods The study involved 61 subjects (age: 30.7 ± 4.9 years old; body mass: 79.4 ± 12.9 kg; body height: 179.6 ± 8.4 cm; 8 woman and 53 man), 31 who trained Brazilian Jiu-Jitsu (BJJ) and 30 subjects who had never trained any combat sport. The mean time of training BJJ in the study population was 3.9 ± 4.1 years. Postural assessments were conducted with the use of the photogrammetric method. The assessment of back pain and injuries was conducted with the Oswestry Disability Index (ODI) and with our proprietary questionnaire. Results Among both populations, 37 subjects reported back pain. There were no differences in back pain location between the two groups or in functional state on the ODI. Significant differences between the groups in the values of the postural parameters (spinal height, length of kyphosis, length of lordosis, pelvis inclination angle) were observed. Statistically significant differences between the NP-BJJ practitioners with and without back pain in the length of the thoracic kyphosis and the differences in the height of the waist triangles were found. Conclusions Both in the study population and in the control group the spinal pain was minimal or moderate on the ODI. BJJ practitioners who reported back pain had characteristic postural changes in some of the analysed postural parameters in comparison to BJJ practitioners who did not report back pain.
Keywords: Martial arts; Body posture; Back pain; Jujitsu; Preventive measures